Separation and Determination of Fe(III) and Fe(II) in Natural and Waste Waters Using Silica Gel Sequentially Modified with Polyhexamethylene Guanidine and Tiron - Svetlana Didukh; Vladimir Losev; Elena Borodina; Nikolay Maksimov; Anatoly Trofimchuk; Olga Zaporogets (Journal of Analytical Methods in Chemistry)
Silica gel, sequentially modified with polyhexamethylene guanidine and pyrocatechin-3,5-disulfonic acid (Tiron), was suggested for sorption separation and determination of Fe(III) and Fe(II). It was found that quantitative extraction of Fe(III) and its separation from Fe(II) were attained at pH 2.5–4.0, while quantitative extraction of Fe(II) was observed at pH 6.0–7.5. An intensive signal with g=4.27, which is characteristic for Fe(III), appeared in EPR spectra of the sorbents after Fe(II) and Fe(III) sorption. During interaction between Fe(II) and Tiron, fixed on the sorbent surface, its oxidation up to Fe(III) occurred. Red-lilac complexes of the composition FeL3 were formed on the sorbent surface during sorption regardless of initial oxidation level of iron. Diffuse reflectance spectrum of surface complexes exhibited wide band with slightly expressed maxima at 480 and 510 nm. Procedures for separation and photometric determination of Fe(III) and Fe(II) at the joint presence and total Fe content determination as Fe(II) in waste and natural waters was developed. The limit of detection for iron was 0.05 μg per 0.100 g of the sorbent. The calibration graph was linear up to 20.0 μg of Fe per 0.100 g of the sorbent. The RSD in the determination of more than 0.2 μg of Fe was less than 0.06.